Quality of life in drug resistant tuberculosis - Chatterjee, Siddharth (International Journal of Research in Medical Sciences, 2022)
Background: India has largest population of drug resistant tuberculosis, the treatment of which is long and full of adverse drug reactions. Despite the ongoing research in clinical and pharmacological aspects, quality of life in drug-resistant tuberculosis remains less explored. Methodology: This hospital based cross-sectional study done in the at tertiary care center in Surat, from January 2019 to February 2020, enrolling patients above 18 years, with multi-drug/ extensively drug resistant tuberculosis, who suffered > 1 adverse drug reaction after commencing treatment. SF-36 was administered and QOL scores calculated in social, mental and physical domains. Results: Among the 120 patients studied, majority(87.5%) were had pulmonary tuberculosis. 92.5% and 7.2% were multi-drug resistant and extensively drug resistant respectively. The quality of life was poor in all three domains- physical (25.1), social (39.5)and mental (39.5). Gender, type of tuberculosis, past history of tuberculosis did not affect the QOL significantly. Conclusion: Drug-resistant tuberculosis along with its associated adverse drug reactions greatly impacts the quality of life in all domains. Measures need to focus not just on treatment of disease but also the adverse drug reactions, rehabilitation and counselling measures as well. Keywords: Drug-resistant Tuberculosis, Adverse drug reactions, Quality of life